Prototype Model for High Speed Railway Power Supply System Suitable for Indian Traction Sub Stations using Multi Modular Converter (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As on 2020, India does not have any globally proven railway lines running with high-speed standards as above 250 km/h. Indian Railways looking at the prospect of high speed rail networks also known as bullet rail network in India. With the present Indian traction supply system which is based on the phase splitting or phase shifting method is not suitable for the high speed railway network unless we eliminate neutral sections as well as mitigating the power quality issues such as voltage unbalance, harmonics and high reactive power drawn from the utility grid. In this paper, Co-phase traction power supply system with zero neutral sections is proposed. Modular multilevel converter based three phase to single phase catenary system through a DC Link has been designed, simulated and laboratory prototype is made. A MATLAB simulation of the suggested method and droop characteristics based on load sharing between the two single phase parallel inverters had executed. The obtained results were satisfactory and shows that the proposed system is very much suitable for high speed railway.